PENGARUH PENGGUNAAN MODEL REALISTIC MATHEMATIC EDUCATION (RME) TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS VIII SMP NEGERI 7 MATARAM TAHUN PELAJARAN 2016/2017 - Anas, Windi Pratiwi; Nissa, Ita Chairun; Abidin, Zainal (Media Pendidikan Matematika, 2017)
This study was aimed to find out the effectiveness of using Realistic Mathematic Education (RME)towards students’ mathematics result learning at the eight students’ of  SMP Negeri 7 Mataram in academic year 2016/2017. In this research, the researcher used quasy experimental research method. The population were all of the eight students of  SMPNegeri7Mataram. the researcher divided into two classes. A class is as control group with 45 number of the students.and B class is as experimental group with 45 number of the students. To collect the data,  the researcher used posttest esay that had been tested the validity and realablity. Based on the result of analysis, the data of posttest was obtained from the students’ score  of expereimental group was 78,58 and control group was 70,04. The data was analyzed by using t-test with significant level 5%. T-test was 2,86 and t-table was 1,99 with degree of freedom (df) = 88. The result of the data showed that  t-test was higher than t-table. It means that Ha is accepted and Ho is rejected. Therefore, the researcher can concluded that the effectiveness of using Realistic Mathematic Education (RME)towards students’ mathematics result learning was effective at the eight students’ of  SMP Negeri 7 Mataram in academic year 2016/2017.